1986
DOI: 10.1073/pnas.83.24.9368
|View full text |Cite
|
Sign up to set email alerts
|

Two DNA recognition domains of the specificity polypeptides of a family of type I restriction enzymes.

Abstract: The hsd genes of Salmonella typhimurium and Salmonella potsdam encode related type I restriction and modification systems designated SB and SP, respectively; the polypeptide encoded by the hsdS gene dictates the DNA sequence recognized. The hsdS genes of the SB and SP systems have a conserved sequence of around 100 base pairs flanked by two nonhomologous (variable) regions of around 500 base pairs. Recombination between the hsdS genes of SB and SP generated a system (SQ) with a different recognition specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…These are considerably more complicated than the type III systems described here (for reviews, see references 6, 7, and 38) but have one property in common with the type III systems: a single polypeptide, the product of the hsdS gene, provides DNA sequence recognition in both restriction and modification. For the family of type I enzymes that includes EcoK, the sequence of the hsdS genes of several family members has been determined (10)(11)(12). The results are amazingly similar to those found with the type III mod genes in that the hsdS genes are also a mosaic of conserved and nonconserved regions.…”
Section: Resultssupporting
confidence: 66%
“…These are considerably more complicated than the type III systems described here (for reviews, see references 6, 7, and 38) but have one property in common with the type III systems: a single polypeptide, the product of the hsdS gene, provides DNA sequence recognition in both restriction and modification. For the family of type I enzymes that includes EcoK, the sequence of the hsdS genes of several family members has been determined (10)(11)(12). The results are amazingly similar to those found with the type III mod genes in that the hsdS genes are also a mosaic of conserved and nonconserved regions.…”
Section: Resultssupporting
confidence: 66%
“…Further work by Gubler and Bickle not only confirmed this hypothesis but also showed the upper and lower limits of such expansion (32). That work supported the growing evidence that type I R-M systems were highly adaptable with respect to their abilities to generate novel DNA specificities, especially through recombination events including domain swapping (4,24,25).…”
Section: Dna Sequence Of the Ecor124i R-m Genessupporting
confidence: 70%
“…The difference between the two specificities was unexpectedly simple: EcoR124I was shown to recognize GAAn 6 RTCG, while EcoR124/3 was shown to recognize the same specific bases but with the inclusion of an extra nonspecific base in the spacer region of the recognition sequence (GAAn 7 RTCG). This was an exciting observation, as it supported the two-domain model for HsdS (originally proposed by Argos [4] and later extended in studies by Murray and others [24,25]) in which a spacer region separates two target recognition domains (TRDs) that bind the specific nucleotides in the recognition sequence. It seemed likely that this spacer was extended in EcoR124/3.…”
Section: Dna Sequence Of the Ecor124i R-m Genesmentioning
confidence: 74%
“…It was shown that the first variable domain specifies the 5h DNA recognition sequence whereas the second specifies the 3h DNA recognition sequence, with a spacing of 6-8 nt between both (FullerPace & Murray, 1986). As a consequence of their structure, variable domains can be swapped between the DNA regions encoding HsdS subunits via crossing-over events, resulting in novel hsdS genes with altered specificities (Fuller-Pace & Murray, 1986). Type I R\M systems have recently been shown to be widespread in lactococci and they could well be the most abundant R\M systems present in this group of bacteria (Schouler et al, 1998a, b).…”
Section: Abbreviations : Abi Abortive Infection ; R/m Restriction/mmentioning
confidence: 99%